(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The cyclo-addition reaction of LH3 (1) with chloroacetyl chloride in the presence of Et3N in dioxane affords the corresponding azetidin-2-one, L’H3 (8). The reaction of 8 with Cu(II), Cd(II), Mn(II), Fe(III) and MoO2(VI) ions in MeOH results in the formation of corresponding coordination compounds, [Cu(OAc)(L’H2)] (9), [Cd(OAc)(L’H2)] (10), [Mn(OAc)(L’H2)(MeOH)2] (11), [FeCl2(L’H2)(MeOH)] (12) and [MoO2(acac)(L’H2)(MeOH)] (13). The compounds have been characterized on the basis of elemental analyses, molecular weight, molar conductance, spectral (IR, reflactance, ESR) and magnetic susceptibility measurements. 8 acts as a monobasic tridentate ONO donor ligand in these monomeric compounds. A square-planar structure for 9, a tetrahedral structure for 10 and an octahedral structure for 11 and 12 have been proposed. 13 affords an eight-coordinate structure.